The Crimes Happened Against Families and Children in Comparative Criminal Law - Issa, Prof. Dr. Hussein Abd Ali (Journal of Legal and Political Studies, 2018)
The study highlights the criminal attacks that affect the family and children in the penal laws of a number of countries, in particular: Germany, Russia, Spain, Switzerland and the Netherlands, in order to explain the main trends of the policy of criminalization and punishment in the face of these crimes and draw up appropriate recommendations for the development of relevant legislation For crimes against the family and children in Iraq in general, and in particular Kurdistan.
Keywords: penal law; policy of criminalization; crime; legislation